Microsoft Power BI Performance Best Practices : a Comprehensive Guide to Building Consistently Fast Power BI Solutions. - Merchant, Bhavik (Packt Publishing, Limited, 2022)
Supercharge performance analytics and create repeatable patterns to ensure you get the best performance and scalability from your analytics solutions with Power BI Key Features Learn how to build performant data models and apply Row-Level Security Identify and fix performance issues in reports, DAX, and datasets using DAX Studio/VertiPaq Analyzer Use a formal process to manage performance, from setting targets to monitoring and remediating issues Book Description This book comprehensively covers every layer of Power BI, from the report canvas to data modeling, transformations, storage, and architecture. Developers and architects working with any area of Power BI will be able to put their knowledge to work with this practical guide to design and implement at every stage of the analytics solution development process. This book is not only a unique collection of best practices and tips, but also provides you with a hands-on approach to identifying and fixing common performance issues. Complete with explanations of essential concepts and practical examples, you'll learn about common design choices that affect performance and consume more resources and how to avoid these problems. You'll grasp the general architectural issues and settings that broadly affect most solutions. As you progress, you'll walk through each layer of a typical Power BI solution, learning how to ensure your designs can handle scale while not sacrificing usability. You'll focus on the data layer and then work your way up to report design. We will also cover Power BI Premium and load testing. By the end of this Power BI book, you'll be able to confidently maintain well-performing Power BI solutions with reduced effort and know how to use freely available tools and a systematic process to monitor and diagnose performance problems. What you will learn Understand how to set realistic performance targets and address performance proactively Understand how architectural options and configuration affect performance Build efficient Power BI reports and data transformations Explore best practices for data modeling, DAX, and large datasets Understand the inner workings of Power BI Premium Explore options for extreme scale with Azure services Understand how to use tools that help identify and fix performance issues Who this book is for Data analysts, BI developers, and data professionals who have learnt the basics of Power BI and now want to understand how to build advanced analytics solutions will find this business intelligence book useful. Familiarity with the major components of Power BI and a beginner-level understanding of their purpose and use cases are required.